Numerical modeling of YSZ droplet impact/spreading with solidification microstructure formation in plasma spraying. (April 2020) - Shen, Mingguang; Li, Ben Q.; Bai, Yu
Highlights: The solution of the Cahn-Hilliard equation to track moving liquid-gas boundaries. A phase field model for polycrystalline growth used to track solid-liquid interface and grain boundaries. Supersonic YSZ droplet impact considered. Convection effect on solidification microstructure investigated. Abstract: A comprehensive numerical model has been developed, which is capable of representing the impact and spreading of a high-velocity yttria-stabilized zirconia (YSZ) molten droplet with microstructure formation in plasma thermal spraying processes. The numerical model entails the explicit finite difference solution of the Navier-Stokes equations and the energy balance equations, coupled with the Cahn-Hilliard equation to track the liquid-gas two phase interface and with a phase field model for solidification microstructure formation involving the polycrystalline growth. Numerical model procedures are given. The model, after being checked for mesh-independence, was applied to study the spreading and solidification of a high-temperature high-velocity YSZ droplet impinging upon a preheated substrate surface under the conditions typical of supersonic plasma thermal spraying processes. Extensive numerical simulations were carried out and results reveal that the solidification microstructure formed in the spreading droplet consists primarily of columnar grains. Computed results are also compared with thermal spray experiments, and gratifying agreement is obtained.